1991
DOI: 10.1002/app.1991.070420625
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of starch polysaccharides and poly(ethylene co‐acrylic acid): Structure and stability in solution

Abstract: SYNOPSISChiroptical methods have been used to study the conformation and interactions of amylose and amylopectin with poly( ethylene co-acrylic acid) (EAA) in aqueous solution. These studies, along with X-ray diffraction and solid-state NMR data, show that amylose and EAA, as well as amylopectin and EAA, form helical V-type inclusion complexes when mixed in aqueous suspension. This structure apparently accounts for the partial compatibility observed in films containing starch and EAA. About 3 by weight of EAA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 25 publications
0
44
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7] However, only limited research has been reported regarding the formation of inclusion complexes between amylose and polymeric compounds. [8][9][10][11][12][13][14] Amylose in solid-state constructs stabilized crystalline structures associated with the formation of double helixes. 15 In addition, single-stranded amylose in an aqueous solution gradually forms a double helix, resulting in a water-insoluble product.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] However, only limited research has been reported regarding the formation of inclusion complexes between amylose and polymeric compounds. [8][9][10][11][12][13][14] Amylose in solid-state constructs stabilized crystalline structures associated with the formation of double helixes. 15 In addition, single-stranded amylose in an aqueous solution gradually forms a double helix, resulting in a water-insoluble product.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hydrophobicity is required as the property of guest molecules to be included by amylose. However, only limited studies had been reported regarding the formation of inclusion complexes composed of amylose and polymeric guest molecules [23][24][25][26][27][28][29]. Because the driving force incorporating guest molecules into the cavity of amylose is the weak hydrophobic interaction, amylose does not have sufficient ability to include the long chains of polymeric guests into its cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Fanta et al [14] and Shogren et al [15] reported that the carboxylic groups of ethylene-acrylic acid (EAA) could form V-type complexes with starch leading to better mechanical properties of blends at higher loadings.…”
Section: Introductionmentioning
confidence: 98%